Grey wolf optimization based clustering algorithm for vehicular ad-hoc networks. (August 2018) - Fahad, Muhammad; Aadil, Farhan; Rehman, Zahoor-ur-; Khan, Salabat; Shah, Peer Azmat; Muhammad, Khan; Lloret, Jaime; Wang, Haoxiang; Lee, Jong Weon; Mehmood, Irfan
Abstract: In vehicular ad-hoc network (VANETs), frequent topology changes occur due to fast moving nature of mobile nodes. This random topology creates instability that leads to scalability issues. To overcome this problem, clustering can be performed. Existing approaches for clustering in VANETs generate large number of cluster-heads which utilize the scarce wireless resources resulting in degraded performance. In this article, grey wolf optimization based clustering algorithm for VANETs is proposed, that replicates the social behaviour and hunting mechanism of grey wolfs for creating efficient clusters. The linearly decreasing factor of grey wolf nature enforces to converge earlier, which provides the optimized number of clusters. The proposed method is compared with well- known meta-heuristics from literature and results show that it provides optimal outcomes that lead to a robust routing protocol for clustering of VANETs, which is appropriate for highways and can accomplish quality communication, confirming reliable delivery of information to each vehicle.